Matching the fellowship training program in gastroenterology with the demands of the profession - Atienza, Melflor A.
The central task of clinical fellowship training programs is preparing trainees for eventual practice. Establishing correspondence between training and practice ensures program relevance and ultimately, quality health care. Given this rationale, the Philippine Society of Gastroenterology (PSG) laid down its core curriculum for the fifteen accredited training hospitals to implement. However, differences in program implementation and new developments in the field of Gastroenterology may affect preparedness of graduates. This study aimed to describe the graduates' professional activities and their perceptions of the adequacy of the program in preparing them for those activities, specifically, in terms of the degrees of preparedness in various areas of competencies and importance of those content areas in practice. This study utilized a cross sectional survey. A questionnaire was circulated to all 50 accessible graduates from 1997-1999. Interviews and review of secondary data were done. An area of competency was described as adequate if there was a match between the degrees of importance and preparedness. A significant discrepancy based on the Wilcoxon Matched-pairs Signed-ranks test was described as underpreparation or over preparation. Thirty-four graduates participated in this study representing 68 percent response rate. All are in clinical practice; most are affiliated with tertiary hospitals in Metro Manila and other cities. They vary significantly in their work schedule, types and number of cases handled. Other activities include research, teaching and administrative functions. Results showed underpreparation in the knowledge component of the program. There was adequate preparation in communication and administrative skills but underpreparation in teaching, research, problem solving, decision-making and clinical skills. Achieving the minimum numbers required by the PSG for diagnostic endoscopic procedures proved to be adequate in preparing respondents for practice. However, there was underpreparation in ERCP and other therapeutic procedures. This was associated with the number of patients and the duration of rotation. The attitudinal component of training was perceived as adequate. Respondents reported adequacy of their preparation in the clinical rotations in the different areas while lectures and conferences were ?somewhat adequate.? Each institution had at least three consultants but it was the time spent with trainees, the amount of supervision and the number of demonstrations that were associated with perception. Except for duodenoscopes and colonoscopes, the availability of facilities was not significantly associated with their perceptions. The study thus showed that to the graduates, an ideal teaching-learning environment is preferred but does not matter as much as the more crucial factors, namely, sufficient clinical cases and quality supervision of consultants. In those areas where there was underpreparation, specifically, knowledge, clinical, research and teaching skills, and therapeutic endoscopic skills, there is much room for improvement in the implementation of the Gastroenterology training program.